Economic Exploitation of Children in Indonesia: An Analysis of Positive Law and Islamic Law - Samuel, Samuel; Badu, Lisnawaty W; Achir, Nuvazria (Yayasan Cahaya Generasi Positif, 2025)
This study delves into the topic of juvenile street performers in Gorontalo City and seeks to understand how well Islamic law and Indonesia's positive legal system work together to protect children from being exploited economically. The economic exploitation of children continues owing to factors such as poverty, familial dependency, insufficient institutional coordination, and limited public awareness, even though there are extensive rules such as the Child Protection Law (Law No. 35 of 2014) and the Manpower Law (Law No. 13 of 2003). This research delves into the theoretical framework and its application via a qualitative juridical-normative lens, bolstered by field observations and an Islamic legal viewpoint. Research shows that despite severe prohibitions and consequences in Indonesia's legal instruments, enforcement is still patchy and reactive, focussing on symptoms rather than causes. Seen through the lens of Islamic law (sharī'ah), the exploitation of children is seen as a breach of the principles outlined in maqāṣid al-syarī'ah, specifically the protection of life (ḥifẓ al-nafs), intellect (ḥifẓ al-'aql), and lineage (ḥifẓ al-nasl). Legal enforcement, education, poverty alleviation, and community-based moral awareness must all be part of a comprehensive plan to effectively safeguard children, which must incorporate positive law with Islamic social and ethical precepts. The research found that for Indonesian children to truly be protected, the legal system must function as a social and moral mechanism based on justice ('adl), compassion (raḥmah), and public welfare (maṣlaḥah), rather than just a prohibitionary tool.